Sensitivity Analysis of Fiber-Reinforced Lamina Micro-Electro-Mechanical Switches with Nonlinear Vibration Using a Higher Order Hamiltonian Approach - Ali Kabiri; Sadegh Sadeghzadeh (Mechanics of Advanced Composite Structures)
In this paper, the nonlinear free vibration of fiber-reinforced lamina micro-switches is investigated, and a sensitivity analysis (SA) is given. The switches are modeled as solid rectangular beams consisting of an isotropic matrix with transversely and longitudinally isotropic reinforcements, incorporating a higher order Hamiltonian approach. An SA of the proposed micro-switch is presented by calculating the numerical derivatives of the presented nonlinear model with respect to the design parameters. The SA of geometric parameters, such as dimensionless length, thickness, initial gap, applied voltage, axial load, and effective modules of the system, was conducted using the Sobol method. It was found that the natural frequency varied when changes were made to the proposed parameters; this finding can be used to optimize future designs.